Empresa extranjera y mercado interno el Ferrocarril Central Mexicano (1880-1907) - Kuntz Ficker, Sandra; Project Muse. (Colegio de Mexico, 1995)
"Extensive landmark study of Mexico's most important railroad line from its inception to its takeover by the Mexican government. Includes massive statistical studies of the railroad's effect on agricultural and mineral production. Concludes that the railroad could modernize Mexico only to the extent that the rest of society permitted"--Handbook of Latin American Studies, v. 58.
Originally presented as the author's thesis (doctoral) under title: El Ferrocarril Central Mexicano, 1880-1907.
Includes bibliographical references (p. 375-383) and index.
Description based on print version record.
Keywords: Ferrocarril Central Mexicano -- History; Investments, Foreign -- Mexico; Railroads -- Economic aspects -- Mexico -- History -- 19th century; Electronic books